PENERAPAN TEKNOLOGI DALAM PENINGKATAN AKUNTANSI SYARIAH - Afiqul Rifqi, Muhammad; Latifah, Eny (JIAR : Journal Of International Accounting Research, 2023)
Technology has a significant impact on the Islamic finance industry, especially in the field of accounting. As time progresses, there are increasing innovations and new breakthroughs in accounting technology. Along with the challenges and opportunities that technology brings to the accounting world, one of the future trends that is expected to make auditing financials easier is AI, artificial intelligence, which greatly assists auditors in their work. IT has already become an integral part of modern accounting, and it will continue to evolve over time, impacting the performance of accountants and the field of Islamic accounting. This research is based on a literature review, which involves gathering data from books, journals, articles, and other sources related to the chosen issue. The results of this research demonstrate a significant impact of technology on Islamic accounting.